"Reversed favoritism" - Resolving the puzzle of discriminatory taxation in African agriculture - Lennart Kaplan (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
The political economy literature highlights the redistribution of resources to political support groups - often along regional or ethnic lines - as a dominant feature of political systems. Against this assumption, Kasara (2007) documents a puzzling result of discriminatory rent extraction by political leaders from farmers in their ethnic home region. Linking a new database on the ethnic and regional affiliation of political leaders to fine-grained survey data, I disentangle ethnic and regional affiliations and show that their intersection explains the phenomenon which I will label in the following "reversed favoritism." More specifically, I provide evidence that agricultural price hikes indeed do not reduce poverty among co-ethnic farmers in the leader's birth region. Results indicate that farmers are aware of the unfavorable taxation as they express lower tax support. Yet, leaders seem to act politically rational as they only apply this treatment in regions where they enjoy high trust. An exploratory analysis suggests that the counter-intuitive support of discriminatory policies can be explained by transfers in other areas, namely development aid.
Keywords: 330